Studi Perilaku Menyimpang: Motif dan Perilaku Kriminal Narapidana dalam Kasus Penganiayaan Kekerasan dalam Rumah Tangga (KDRT) - Ciek Julyati Hisyam; Rini Krisna Dewi; Atika Maharani Deya; Salsabila Adistiani; Jalmi Katulistiwa; Zahra Huseinah; Ihsan Fadhiilah (Universitas 45 Surabaya, 2024)
Domestic violence (DV) is a form of social deviation that violates norms in a family and society. Domestic violence is often triggered by emotional tension and interpersonal conflict, such as betrayal by a partner. This study aims to identify the motives of perpetrators of domestic violence and the factors that influence this criminal behavior. The method used in this study is a qualitative approach with in-depth interviews with prisoners involved in domestic violence cases. The results of the study indicate that uncontrolled emotions, relationship tensions, and poor communication are the main factors that trigger violence. This phenomenon illustrates the importance of emotional management and rehabilitation to prevent the recurrence of domestic violence.